Perilaku Konsumen Terhadap Keputusan Pembelian Lapis Kukus Pahlawan Surabaya - Fira Feriyadita; Novi Diana Badrut Tamami (LPPM Universitas Trunojoyo Madura, 2021)
Lapis kukus pahlawan is known as a typical Surabaya food whose official branches are spread in several corners of the city. The high competition in the culinary industry in the cake business has resulted in increasingly fierce market competition. This triggers Lapis kukus pahlawan surabaya to understand the characteristics and behavior of consumers. The purpose of this study are to understand the consumer characteristics of lapis kukus pahlawan surabaya and to analyze the influence of consumer behavior on purchasing decisions of lapis kukus pahlawan surabaya. The analytical method used in this research is quantitative descriptive analysis using multiple linear regression test. The results of the study explain that the majority of consumers of lapis kukus pahlawan surabaya are aged 17-25 years, female, working as a private employee from Surabaya, Sidoarjo Bangkalan, income per month is less than 1,000,000 and the last education is high school / equivalent. Simultaneously, cultural factors, social factors, personal factors and psychological factors influence consumer purchasing decisions. While partially cultural, social, personal and psychological factors influence purchasing decisions, but the most dominant are psychological factors. The resulting implication is to create an effective marketing strategy to attract consumer buying interest.